2016
DOI: 10.1088/1748-6041/11/1/015012
|View full text |Cite
|
Sign up to set email alerts
|

Bone ingrowth of various porous titanium scaffolds produced by a moldless and space holder technique: anin vivostudy in rabbits

Abstract: Porous titanium has long been desired as a bone substitute material because of its ability to reduce the stress shielding in supporting bone. In order to achieve the various pore structures, we have evolved a moldless process combined with a space holder technique to fabricate porous titanium. This study aims to evaluate which pore size is most suitable for bone regeneration using our process. The mixture comprising Ti powder, wax binder and PMMA spacer was prepared manually at 70 °C which depended on the mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…Gauthier et al showed that after 8 weeks of in vivo implantation, better bone ingrowth was achieved for ceramic scaffolds with macropores of 565 μm than 300 μm. On the other hand, Prananingrum et al showed that the pore size of 100 µm presented the greatest amount of bone ingrowth, and the rate of bone ingrowth significantly decreased as the pore size increased on Ti scaffolds. Torres‐Sanchez et al concluded that small pores offer a larger surface area and at early days of culture this pore size is favorable for the attachment stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gauthier et al showed that after 8 weeks of in vivo implantation, better bone ingrowth was achieved for ceramic scaffolds with macropores of 565 μm than 300 μm. On the other hand, Prananingrum et al showed that the pore size of 100 µm presented the greatest amount of bone ingrowth, and the rate of bone ingrowth significantly decreased as the pore size increased on Ti scaffolds. Torres‐Sanchez et al concluded that small pores offer a larger surface area and at early days of culture this pore size is favorable for the attachment stage.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium is a widely used material in biomedical implants due to the combination of the required properties, as excellent corrosion resistance, adequate biocompatibility, and mechanical properties . However, the differences between the Young's modulus of the Ti implants and the bone (110 and 10–30 GPa, respectively) leads to stress shielding effect on the supporting bone .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pore sizes of 100µm have been reported to be favourable for bone tissue ingrowth (Prananingrum et al 2016), and the scaffolds produced here are thus of suitable dimensions for bone ingrowth, and can moreover be tuned for precise control of dimensions.…”
Section: Density and Porosity Of Titanium Alloy Scaffoldsmentioning
confidence: 90%
“…Moreover, cells from the surrounding must be able to penetrate. Pore size is, thus, an important feature since if the pores are too small, pore occlusion by the cells will happen and it is also an important factor for protein adsorption, cellular migration and osteoconduction [11,71]. Pore sizes greater than 300 µm are recommended for bone ingrowth in comparison with smaller pore size [67,[72][73][74].…”
Section: Scaffolds-based Tissue Engineeringmentioning
confidence: 99%